The development of emotional face and eye gaze processing - Höhl, Stefanie; Striano, Tricia (Developmental science, 2010)
Recent research has demonstrated that infants’ attention towards novel objects is affected by an adult’s emotional expression and eye gaze toward the object. The current event-related potential (ERP) study investigated how infants at 3, 6, and 9 months of age process fearful compared to neutral faces looking toward objects or averting gaze away from objects. Furthermore, we examined how the processing of novel objects is affected by gaze direction and emotional expression. We hypothesized that an adult’s fearful expression should be particularly salient when it is directed toward a referent in the environment. Furthermore, responses to objects should be increased if the face previously expressed fear toward the object. Three-month-olds did not show differential neural responses to fearful vs. neutral faces regardless of gaze direction. Six-month-olds showed an enhanced negative central (Nc) component for fearful relative to neutral faces looking toward objects, but not when eye gaze was averted away from the objects. Furthermore, 6-month-olds showed an enhanced Nc for objects that had been gaze-cued by a fearful compared to a neutral face. Nine-month-olds showed an enhanced Nc for fearful relative to neutral faces in both eye gaze conditions and showed an enhanced Nc for objects that had been gaze-cued by a neutral face. The findings are discussed in the context of social cognitive and brain development.
First published: 04 January 2010
Gesehen am 28.02.2023